PEMBELAJARAN SASTRA DI SEKOLAH DASAR BERBASIS KEARIFAN LOKAL (CERITA RAKYAT) - Sumayana, Yena (Universitas Pendidikan Indonesia, 2017)
Folklore is one of the literary works that can specifically be used as teaching materials and help students to recognize local wisdom. In addition, folklore also serves as a medium of learning and entertainment and fostering emotional intelligence in students. Local wisdom owned by each region certainly has positive values for the development and character of children and can foster a love of regional culture. Folklore can also introduce the culture of the archipelago to students and can also take advice from the folklore as one of character education. This article seeks to provide ideas on the development of local wisdom in this folktale to be used as a source of literary learning materials so that folklore can be an alternative source of teaching materials by teachers during the learning process.Keywords: literacy learning, local wisdom, folklore.